Defining the Factors for Development of Managerial Staff as a Means of Increasing Its Efficiency - Schevchenko Viktoriia S.; Bіda Svіtlana S. (Bìznes Inform, 2019)
The publication forms a model to increase the efficiency of managerial staff. It was found that, in practice, depending on the organization’s situation, one or several consolidated methods can constitute the base for determining certain needs for development. In order to identify the main directions of development of managerial staff and evaluate its efficiency, the authors propose for medium and small organizations the usage of a combination of two informal methods: the method of work and profession and the method of desire of the staff. It is defined that the main task of developing managerial staff should consist in improving the knowledge required by the manager and the professional in the implementation of managerial functions. In this regard, it is important to define what knowledge needs to be developed and improved. The importance of knowledge for certain categories of managerial staff should therefore be defined. This will serve as a basis for developing training programs for the organization’s managers and professionals to increase their competitiveness. It is defined that the main purpose of training through activities is that such a training allows to minimize the time to develop both individual and collective creativity potential of employees, to bring their knowledge and skills closer to practical needs, accelerate their capitalization. The training through activities activates the desire to master ways of solving unique problems on one’s own, as well as formulating the content of these problems. There is another feature of the development of modern education in the organization. It is substantiated that in order for the system of improving the efficiency of managerial staff to function efficiently, an effective mechanism for administration of its development must be formed and implemented in practice. It is identified that the essence of administration of a system of increasing the managerial staff efficiency is a targeted impact on the object of development (managerial staff) that sets a change in its capabilities to fit the needs of the professional experience of the organization. Moreover, the organization may lack a number of elements of the system of administration of professional development - the functions of these elements are delegated to specialized higher education institutions.